Scheme of obtaining ß-carotene standard from pumpkin (Cucurbita moschata) flesh - Shahidan, Norshazila; Jaswir, Irwandi; Othman, Rashidi; Hashim, Yumi Zuhanis Has-Yun (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2012)
Characterization and quantification of carotenoid compound is complicated, costly and timeconsuming. The accuracy and reliability of the data depend solely on the standard and to High Performance Liquid Chromatography (HPLC) analysis but the major constraint is to acquire and to maintain the pure standards. Carotenoid standards are commercially available but they are expensive and are prone to isomerization and oxidation. Thus, the purpose of this study is to establish an analytical method for isolating β-carotene by using open column chromatography (OCC) from pumpkin (Cucurbita moschata) to be used as one of the carotenoid standards for determination of total and individual carotenoid. Pumpkin with orange flesh has been chosen due to the non-seasonal nature and its availability all year-round. This study demonstrated that the purity of β-carotene standard; determined by HPLC was ranged from 92.21 to 97.95%. The standard curves with five different concentrations of β-carotene extract from pumpkins in triplicate were constructed by plotting the peak area against the concentration. The coefficient of correlation was 0.9936. Therefore, this study established that pumpkin can be a reliable source of beta-carotene standard as it is cheap and commonly available throughout the year.